Role of the Supply Chain Finance Application in Indonesian Listed Banking Industries - Syamsudin, Syamsudin; Noormala Dewi, Syahrina; Nuryulia Praswati, Aflit (ExcelingTech, 2020)
The issue of supply chain management has been raised for nearly three decades, and based on available statistics, countries and organizations that have applied this knowledge have made significant progress in their respective fields and have made huge profits and large financial savings. In this study, while examining the existing infrastructure and the needs of the bank to enter the financing industry as one of the links in the supply chain of banks, the current state of the capital market and financing companies to the title of financing leaders was examined. Also, the profitability of financing companies and their types of services were studied and various methods of entering the industry were studied. In this regard, the strengths and weaknesses of entering the financing market as well as the opportunities and threats ahead were examined. In the end, the scheme of received commissions and hypothetical profit was proposed. One mechanism used to establish good supply chain management is the existence of a monitoring and monitoring system. The supply chain management mechanism in this study is shared with an internal mechanism proxy by an independent audit committee, audit committee financial expertise, frequency of audit committee meetings, managerial ownership, and an independent board of commissioners. The external mechanism is proxied by leverage. The population in this study is all banks that go public and are listed on the Indonesia Stock Exchange. This study uses a purposive sampling method, which is a sample based on the suitability of the characteristics of the sample with the specified sample selection criteria, with the following criteria: (1) Banks listed on the Indonesia Stock Exchange from 2015– 2017; (2) The Bank publishes annual reports from 2015 - 2017 and is published on the IDX website or the company's official website; (3) Having complete data relating to the variables used in this study. This study finds that most of the samples, management did not own the company's shares, besides that there was also no clear definition of financial expertise that must be owned by the audit committee. Studies have shown that the bank completes its supply chain by establishing a financing company while earning a profit and ensures the retention of current customers while getting potential customers.